Peran Guru PAI dalam Pembentukan Karakter Religius Siswa di MTs Zahrotul Islam Kota Probolinggo - Jayani, Ahmad; Nuha, Nazahah Ulin (Lembaga Yasin AlSys, 2025)
This study aims to explore the role of Islamic Religious Education (PAI) teachers in shaping the religious character of students at MTs Zahrotul Islam in Probolinggo City. The implementation of PAI education in this institution is not limited to academic or cognitive aspects but also encompasses a broader religious dimension. MTs Zahrotul Islam is committed not only to imparting religious knowledge but also to fostering individuals with strong moral and religious character. This study employs a descriptive qualitative method with source triangulation, involving the principal, PAI teachers, and students for data validation. The data analysis technique follows Spradley’s model, utilizing a componential analysis approach to identify relevant domains and verify data accuracy. The findings indicate that the role of PAI teachers in shaping students’ religious character can be analyzed through an academic approach based on educational theory and empirical studies. PAI teachers serve not only as facilitators in transmitting religious knowledge but also as role models who significantly influence students' behavior, ethics, and social interactions. This study highlights the necessity of a systematic approach that integrates educational policies with innovative learning strategies, including extracurricular activities based on Islamic values. Thus, the role of PAI teachers in fostering students’ religious character at MTs Zahrotul Islam is not merely instructional but also transformative in shaping a generation with strong moral integrity and adherence to Islamic principles.